Awareness, familiarity and usage of traditional research metrics and altmetrics among academics in Malaysia - Keng, Siau-Ting; Ooi, Pei-Boon; Pang, Khong-Yun; Phan, Chia-Wei (Malaysian Journal of Library and Information Science, 2022)
The growing necessity to improve the evaluation methods of research impact as scholarly communication has progressed increasingly online. Studies investigating awareness and usage of social media among academics have been increasing. However, only limited studies focus on the familiarity and usage of research metrics among them. The aim of the study was to investigate the relationship between awareness, familiarity, and usage, as well as hindrances in using research metrics among academics in Malaysia. A total of 344 individuals took part in an online survey and the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to examine the postulated hypotheses. Our results revealed that familiarity is the only predictor associated with the usage of research metrics among academics with 62.7% of variance explained. Seniority did not mediate the relationship between familiarity and awareness to the usage of research metrics among academics. In conclusion, altmetrics have the potential to develop as complements to traditional metrics and to provide a useful insight into new impact modes not included in existing measures.